Assessing the influence of gastrocnemius reconstruction on stress distribution of femoral tumor rotating hinge knee prosthesis via finite element analysis - Jiang, Jie; Zeng, Fanwei; Tang, Xiaodong (Frontiers in Bioengineering and Biotechnology, 2024)
Background: After femoral oncological knee arthroplasty, some patients suffer from rotating axis fracture, which significantly impacts the life span of the rotating hinge knee (RHK) prosthesis. This research aimed to analyze the biomechanical response of anatomical gastrocnemius reconstruction and assess whether it could reduce the risk of rotating axis breakage by finite element (FE) analysis. Methods: A femur-prosthesis-tibia FE model was established using the data from CT scans. The mechanical properties of the RHK implant were quantitatively compared before and after gastrocnemius reconstruction at 6 angles: 10°, 20°, 30°, 40°, 50°, and 60°. Results: Our results showed that gastrocnemius reconstruction effectively altered the stress distribution around the rotating axis, considerably relieving the stress in the fracture-prone region. In addition, the peak strain in the rotating axis, bending axis, prosthesis stem, and femoral condyles decreased variably. Conclusions: In distal femoral resection knee arthroplasty, the rebuilding of gastrocnemius substantially improved the stress distribution within the prosthesis, thereby having the potential to reduce the risk of prosthetic fracture and prolong the overall durability of the prosthesis.